Efeitos biológicos da Pfaffia glomerata (Spreng.) Pedersen e da Pfaffia paniculata (Martius) Kuntze (Amaranthaceae) Biological effects of Pfaffia glomerata (Spreng.) Pedersen and Pfaffia paniculata (Martius) Kuntze (Amaranthaceae) - Diógenes Aparício Garcia Cortez (Acta Scientiarum : Biological Sciences, 1999)
A Pfaffia glomerata (Spreng.) Pedersen e da Pfaffia paniculata (Martius) Kuntze (Amaranthaceae) são plantas nativas da região alagada das ilhas de Porto Rico, Paraná, Brasil. São utilizadas na medicina popular como tônico, afrodisíaco e antidiabético. O extrato bruto metanólico, obtido das raízes das duas espécies, foi utilizado para avaliar a atividade moluscicida de caramujos (Biomphalaria glabrata). Além disso, o potencial hipoglicemiante da Pfaffia glomerata foi investigado em ratos tratados com aloxana. As saponinas do extrato bruto metanólico da P. glomerata e da P. paniculata foram analisadas em cromatografia em camada delgada e foi determinado o índice hemolítico. O extrato bruto metanólico obtido da Pfaffia glomerata apresentou maior conteúdo de saponinas hemolíticas e maior atividade moluscicida em relação à Pfaffia paniculata. Todavia, o tratamento com extrato de Pfaffia glomerata não promoveu efeitos significativos sobre os níveis glicêmicos. Pfaffia glomerata (Spreng.) Pedersen. (Amaranthaceae) and Pfaffia paniculata (Martius) Kuntze are native plants found in the flooded area of the islands of Porto Rico, state of Paraná, Brazil. They are used in folk medicine as tonics, aphrodisiacs, and to treat diabetes. The methanolic extract obtained from roots of both species was used to evaluate the molluscicidal activity against the periwinkle Biomphalaria glabrata and the hypoglycemic activity of Pfaffia glomerata was investigated in rats with diabetes induced by alloxan. The saponins from the methanolic extract of P. glomerata and P. paniculata were analyzed by thin-layer chromatography and scum and the hemolitic index was measured. The methanolic extract obtained from Pfaffia glomerata showed higher content of hemolytic saponin than Pfaffia paniculata and presented molluscicidal activity against Biomphalaria glabrata from 200 ppm. However, the treatment with P. glomerata extract did not promote any significant effect on glycemic levels.